2016
DOI: 10.1021/acs.biochem.6b00480
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of p300/CBP Acetylation of Nucleosomes by Bromodomain Ligand I-CBP112

Abstract: The histone acetyltransferase (HAT) enzymes p300 and CBP are closely related paralogs that serve as transcriptional coactivators and have been found to be dysregulated in cancer and other diseases. p300/CBP is a multidomain protein and possesses a highly conserved bromodomain that has been shown to bind acetylated Lys residues in both proteins and various small molecules, including I-CBP112 and CBP30. Here we show that the ligand I-CBP112 can stimulate nucleosome acetylation up to 3-fold while CBP30 does not. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 42 publications
2
42
1
Order By: Relevance
“…Binding of Ac-K1596 to the BRD is likely to be enhanced within the intact CBP catalytic core due to its increased effective concentration. In contrast to our observations with ischemin, the bromodomain inhibitor I-CBP112 activates CBP/p300 toward acetylation of a subset of H3 and H4 residues (H3K18, H3K23, H4K5) within nucleosomal substrates, whereas a different inhibitor, CBP30, has no effect on histone acetylation (46). It is…”
Section: Negative Regulation Of Histone Acetyltransferase Activity Bycontrasting
confidence: 99%
“…Binding of Ac-K1596 to the BRD is likely to be enhanced within the intact CBP catalytic core due to its increased effective concentration. In contrast to our observations with ischemin, the bromodomain inhibitor I-CBP112 activates CBP/p300 toward acetylation of a subset of H3 and H4 residues (H3K18, H3K23, H4K5) within nucleosomal substrates, whereas a different inhibitor, CBP30, has no effect on histone acetylation (46). It is…”
Section: Negative Regulation Of Histone Acetyltransferase Activity Bycontrasting
confidence: 99%
“…This activation of acetylation is seen both in vitro and in cell culture. The requirement of p300/CBP domains beyond the HAT domain and the intact nucleosome substrate points toward a multifaceted interaction shift propagated by I-CBP112, potentially unique to this bromodomain ligand among other small molecules [53]. The importance of the bromodomain to activate p300 acetylation was consistent with an earlier study in which deletion of the bromodomain abolished p300 acetylation of an entire library of nucleosome substrates [54].…”
Section: Multi-domain Regulation Of P300/cbpsupporting
confidence: 75%
“…Six compounds were identified that displayed substantial induction of JK-1 cell differentiation. Significantly, four of the six top compounds included inhibitors of bromodomain-containing proteins: two compounds, (+)-JQ1 (45) and PFI-1 (46), target mammalian bromodomain and extra terminal domain (BET) proteins; bromosporine is a general bromodomain inhibitor (47); and I-CBP112 targets the bromodomain of cAMP-responsive element-binding protein binding protein (CREBBP)/E1A-associated protein p300 (EP300) (48,49). The only other bromodomain-specific inhibitor in the library, PFI-3, targets a different category of bromodomaincontaining proteins (50) and was not found to be an inducer of JK-1 differentiation.…”
Section: Resultsmentioning
confidence: 99%